Lignins and Their Derivatives with Beneficial Effects on Human Health - Vinardell, Maria Pilar (Int J Mol Sci, 2017)
A review of the pharmacological applications of lignins provides evidence of their protective role against the development of different diseases. In many cases, the effects of lignins could be explained by their antioxidant capacity. Here, we present a systematic review of the literature from the period 2010–2016 which provides information concerning new applications of lignins derived from recent research. The most promising findings are reported, including the methodologies employed and results obtained with lignins or their derivatives which may improve human health. We highlight potential applications in the treatment of obesity, diabetes, thrombosis, viral infections and cancer. Moreover, we report both that lignins can be used in the preparation of nanoparticles to deliver different drugs and also their use in photoprotection.